Women and Children Empowerment through Learning English: Collaborating with Jage Kestare Foundation - Puspita Dewi; Riyana Rizki Yuliatin; Isra Dewi Kuntary Ibrahim; Nurul Hidayah; Raden Bagus Faizal Irany Sidharta; Ni Gusti Ayu Dasriani (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
English as a lingua Franca has special attention for people or children to learn the skill including for children and young people in Ungga village. It is because the language is one of the tools to communicate with other people such as for education, business, tourism, politics, and other sectors. Ungga has a good potency to be developed in promoting the village to be one of the tourism places in central Lombok because it is near to the Mandalika spots. Consequently, human resources are needed to be prepared related to the knowledge and the skills. One of the ways to achieve the goals is providing English training either for young people or for children. Teaching English has numerous challenges. However, designing collaborative learning with some games would encourage them in learning. Children enjoy playing games both online or offline with peers or friends so that collaborative learning by designing a fun concept is one of the effective ways to teach and learn English. Several games were provided such as guess voices, mix, and match, and Find Friends. Besides, partnership among universities, village officers, and communities is crucial to maintaining sustainability so that the university collaborated with one of the communities in the village “Jage Kestare Foundation” to conduct the activity. Teaching English learning goal is not only for learning English but also incorporating gender equality values in the teaching and learning process through materials and activities. The results of the community service activity are that the learners become more active in learning English and more aware of gender equality values. It is expected that by empowering the women and children in the village through learning English by incorporating gender values, it will be able to empower the communities particularly for women and children, and to gain revenue-generating.